(untitled) (Third Sector Social Economic Review, 2022)
The Covid-19 epidemic, which continues to exist, has caused socio-cultural, health, economic and psychological changes. At the beginning of these changes is consumer behavior. Generation Z, which accounts for about a third of the world’s population, has a significant impact on purchasing decision processes. Generation Z has efficiency and trend-setting features in purchasing decision processes. For this reason, it is important to determine the consumption behaviors in an extraordinary period such as Covid-19. The aim of the study is to evaluate the change of Z Generation Consumer Behaviors from the Covid-19 Process to the Post Covid-19 Period. Then, predictions will be made about how consumer behavior will be in the Post-Covid period. In the study, the case study method, which is one of the qualitative research designs, was preferred. Data were collected through structured interview forms with 40 university students determined by criterion sampling. The obtained data were subjected to content analysis with the MAXQDA package program. As a result of the analysis, there are a total of five themes under the category of consumer behavior in the Covid-19 process. These themes are; products, services and sectors, shopping frequency duration and payment amounts, shopping attitude, new consumer behavior after shopping, shopping platforms and payment methods.